Getting incentives right? a comparative analysis of policy instruments for livestock waste pollution abatement in Yucatan, Mexico - Drucker, Adam G. (Cambridge University Press, 2003)
Building on the extensive theoretical and empirical work regarding the cost-minimizing properties of economic instruments, this article describes and analyses the Mexican legislation relevant to the treatment/disposal of pig slurry in the state of Yucatan. Using a linear programming model to determine the optimal level of pig production and abatement processes simultaneously, different policy instruments and scenarios are compared. Serious shortcomings associated with the recently introduced command and control (CAC) legislation, which establishes concentration based standards for discharges, are identified. It is shown that it will be extremely difficult and expensive to comply with (cost: US$41.8 million per annum). An alternative mass based CAC approach, which instead regulates nitrogen applications to land, has compliance costs of US$3.5 US$9.4 million per annum, depending on the strictness of the standard. By contrast, an environmentally equivalent economic instrument approach results in additional cost savings of 22 25 per cent. The results are of relevance to Mexican policy makers, extensionists, researchers, and farmers.